2016
DOI: 10.1177/1087054716669226
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Characteristics of ADHD and Obsessive-Compulsive Disorder Comorbidity

Abstract: Objective: To investigate the clinical implications of obsessive-compulsive disorder (OCD) and ADHD comorbidity in adults. Method: The OCD patients who had and had no diagnosis of adulthood ADHD were compared in terms of several demographic and clinical variables. Results: The mean number of obsessions and compulsions; hoarding, symmetry, and miscellaneous obsessions; ordering/arranging and hoarding compulsions; total, attentional, and motor subscale scores of Barratt Impulsivity Scale (BIS)-11 were more frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…In adults, however, the presence of ADHD in OCD subjects has been rarely investigated and few studies have examined possible correlates of this comorbidity (Anholt et al, ; Frost, Steketee & Tolin, ; Jaisoorya, Reddy & Srinath, ; Mancebo et al, ; Mersin Kilic, Dondu, Memis, Ozdemiroglu & Sevincok, ; Pinto et al, ; Ruscio, Stein, Chiu & Kessler, ; Sheppard et al, ; Tolin & Villavicencio, ). These studies have reported rates of ADHD in adult OCD patients ranging from 0% (Jaisoorya et al, ) to 44.4% (Mersin Kilic et al, ; Table ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In adults, however, the presence of ADHD in OCD subjects has been rarely investigated and few studies have examined possible correlates of this comorbidity (Anholt et al, ; Frost, Steketee & Tolin, ; Jaisoorya, Reddy & Srinath, ; Mancebo et al, ; Mersin Kilic, Dondu, Memis, Ozdemiroglu & Sevincok, ; Pinto et al, ; Ruscio, Stein, Chiu & Kessler, ; Sheppard et al, ; Tolin & Villavicencio, ). These studies have reported rates of ADHD in adult OCD patients ranging from 0% (Jaisoorya et al, ) to 44.4% (Mersin Kilic et al, ; Table ).…”
Section: Introductionmentioning
confidence: 99%
“…In adults, however, the presence of ADHD in OCD subjects has been rarely investigated and few studies have examined possible correlates of this comorbidity (Anholt et al, ; Frost, Steketee & Tolin, ; Jaisoorya, Reddy & Srinath, ; Mancebo et al, ; Mersin Kilic, Dondu, Memis, Ozdemiroglu & Sevincok, ; Pinto et al, ; Ruscio, Stein, Chiu & Kessler, ; Sheppard et al, ; Tolin & Villavicencio, ). These studies have reported rates of ADHD in adult OCD patients ranging from 0% (Jaisoorya et al, ) to 44.4% (Mersin Kilic et al, ; Table ). Some of these studies have reported that the OCD + ADHD comorbidity in adults was associated with an earlier onset of the OCS (Mancebo et al, ; Mersin Kilic et al, ), and higher frequencies of the symmetry/ordering (Mersin Kilic et al, ), aggression (Anholt et al, ), contamination (Anholt et al, ), miscellaneous (Mersin Kilic et al, ), and hoarding (Mersin Kilic et al, ; Sheppard et al, ) symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations